PERAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DALAM MENINGKATKAN PENGARUH KUALITAS KEHIDUPAN KERJA DAN KESEIMBANGAN KERJA-HIDUP TERHADAP KEPUASAN KERJA PADA RUMAH SAKIT UMUM - Achyarnis, Achyarnis; Imronudin, Imronudin; Ichsan, Burhannudin (Jurnal Manajemen Terapan dan Keuangan, 2024)
This study aims to develop the concept of quality of work life and work-life balance on job satisfaction and use work motivation as a mediating variable. Data collected were 162 respondents consisting of lower, middle, and upper level employees at the Rizky Amalia General Hospital, Sragen, Central Java, Indonesia. Quantitative approach with questionnaire survey as data collection and statistical analysis with Smart PLs to prove the hypothesis built. The findings show that quality of work life and work-life balance have a significant positive effect on job satisfaction and work motivation both directly and indirectly with work motivation mediation. This study focuses on all employees at the Rizky amalia Hospital consisting of doctors, directors, managers, management staff, field staff (security, office boy, cleaning service, laundry, etc.), and medical personnel (pharmacy, nutrition, nurses, midwives, laboratory analysis, etc.). The contribution of this study is the development of the concept of a motivation model as a mediating variable that has not been developed by previous studies so that it becomes a model that has conceptual novelty.